About Writing and Journals - Hüllmann, Joschka A. (Satura, 2018)
Writing is a cognitive process with three phases that are entangled: planning, translating, and reviewing. Very roughly, planning is the phase of building a tacit representation of what you want to write in your mind. Translating is to explicate the tacit representation and to put it into visible language, and reviewing is to evaluate and revise. The phases are intertwined and do not occur in a linear sequence. Instead, the writer cycles through the phases multiple times in different orders, making writing an iterative cognitive process. As part of the recurring planning phase, the internal representation of what the writer has in mind changes, developing the argument further. Developing the argument is essential for compelling writing and conducting science, as for scholars, writing is a crucial instrument.